2022
DOI: 10.1108/msar-06-2022-0029
|View full text |Cite
|
Sign up to set email alerts
|

Online brand advocacy for sustainable brands: a study in an emerging market

Abstract: PurposeThe main aim of this study is to integrate the theory of planned behavior (TPB) to examine consumers' intention to advocate for sustainable brands, whilst incorporating the moderating role of pro-environmental self-identity. Consumer sustainability orientation is also added as an antecedent for attitudes to determine the degree to which consumers' personal convictions and attitudes toward sustainability impact their attitude toward sustainable brands. The importance of using the TPB to study online bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…As a result, they began creating online content, such as giving feedback and writing user reviews for others when they had positive or negative experiences with products or services. In this sense, their behaviours align with younger people; when perceiving themselves as informed and educated about a brand, they are compelled to communicate their in-depth cognition and intimate knowledge of that brand with others (Abdelrazek and El-Bassiouny, 2022). Nonetheless, when recommending their favourite brands to others, which older consumers do constantly and willingly, they prefer to do so in-person with their inner circle of friends and families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they began creating online content, such as giving feedback and writing user reviews for others when they had positive or negative experiences with products or services. In this sense, their behaviours align with younger people; when perceiving themselves as informed and educated about a brand, they are compelled to communicate their in-depth cognition and intimate knowledge of that brand with others (Abdelrazek and El-Bassiouny, 2022). Nonetheless, when recommending their favourite brands to others, which older consumers do constantly and willingly, they prefer to do so in-person with their inner circle of friends and families.…”
Section: Discussionmentioning
confidence: 99%
“…The study is congruent with Chiosa and Anastasiei's (2018) research, which found that a positive attitude is the most crucial factor determining consumer intention to become brand advocates. Abdelrazek and El-Bassiouny (2022), who studied millennial consumers, also indicated that consumers could not advocate for a brand online without a positive attitude and strong brand confidence. The current study examines positive attitudes and discusses insights into older consumers' behaviours, which reflect the four OBA dimensions proposed by Wilk et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g. Ali, 2022;Van Tonder et al, 2020) have acknowledged that when customers achieve desired outcomes through their interactions with a brand, they are likely to share positive emotions, behaviors, and thoughts with others, which can manifest as actions such as sharing brand information and having a positive attitude toward the brand (Abdelrazek and El-Bassiouny, 2023;Kim et al, 2023). Therefore, in this study, brand positivity and brand information sharing were chosen as two forms of customer pro-social behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The rising concern over socio-ecological problems indicates the growth of environmentally and socially conscious consumers (Abdelrazek & El-Bassiouny, 2022). On similar lines, NielsenIQ (2018) (a multinational market research company) conducted a survey in which 81% of participants strongly voted that businesses should work for the betterment of the environment.…”
Section: Introductionmentioning
confidence: 99%